Who was Harriet Beecher Stowe? - Rau, Dana Meachen, 1971- (Grosset & Dunlap, 2015)
Examines the life of the nineteenth-century author famous for the novel "Uncle Tom's Cabin," which denounced slavery and intensified the disagreement between the North and South.